Corrosion behaviour of aluminium alloy treated with vegetable and mineral oil lubricationts in NaCI medium - W.B., Wan Nik; Z. Alias; Mohammed Misbahul, Amin (Oriental Science Publishing Co, 2009)
Link to publisher's homepage at http://www.orientjchem.org/